Journeys of discovery in volunteer tourism : international case study perspectives (CABI, 2008)
This book explores the experiences of the volunteer tourist and the ensuing narratives between host and volunteer as it manifests in diverse and increasingly contested political international contexts. As such, this volume includes case studies conducted in 12 countries across six continents. The book is organized into three parts that explore key approaches to, and dimensions of, volunteer tourism. Part I (chapters 1-5) considers the perspectives of host communities and the organizations that provide them with volunteers as part of a process of social and community development. Part II (chapters 6-11) presents case studies that focus upon the experiences of the volunteer tourist and considers issues of the self, motivation, identity and the impact of volunteer tourism upon the volunteer. The case studies presented in part III (chapters 12-16) consider new and emerging trends that challenge traditional conceptualizations of volunteer tourism and open the door for further investigation that explores their implications in the future. This concluding part asks questions about the future of volunteer tourism and the dialogue that arises if we examine how a commodified or decommodified frame is used to examine it. This book was developed as a resource for scholars, commercial and non-commercial providers and students alike. It has a subject index.